Process and quality of peer review in scientific Nursing journals - Wai Tong Chien (MDPI AG, 2011)
To be high quality and international recognized scientific journal for health care professions, such as medical and nursing disciplines, a well-structured and effective peer review system is of an utmost importance. Beckstead (2009) in his guest editorial published in the September issue of International Journal of Nursing Studies suggested that it was important for authors, as well as editors and publishers, to have a clear understanding of whom the intended readers of the journal are; and for the peer reviewers, to answer a key question: whom are we writing to? and more importantly, to assure a transparent, rigorous and quality peer-review. Their questions and declarations stimulated us to think about two important issues: first, the importance of a high quality and effective peer-review in a scientific nursing journal and second, the peer-review system, its monitoring and contribution to quality improvement.